INDUCTION OF LABOUR IN POSTDATE PREGNANCIES A COMPARATIVE STUDY BETWEEN ISOSORBIDE MONONITRATE PLUS MISOPROSTOL VS MISOPROSTOL ALONE AS A METHOD OF INDUCTION OF LABOUR - Nadeem Shahzad; Naila Akram; Asif Hanif (Journal of University Medical & Dental College, 2015)
ABSTRACT BACKGROUND: Postdate pregnancies are the pregnancies beyond the expected date of delivery, posterm pregnancies are also included in the classiﬁcation of postdate pregnancies which lasts more than 42 weeks or 294 days calculated after the ﬁrst day of last menstrual period. Intrapartum and postpartum obstetric complications are enormous in post term pregnancy and is associated with higher perinatal morbidity and mortality rates. Postdate pregnancy is one of the major indication of induction of labour. There is plethora of techniques available for labour induction. OBJECTIVES: To compare the efﬁcacy of intra vaginal use of Isosorbide Mononitrate (IMN) plus Misoprostol versus Misoprostol alone for induction of labour in postdates pregnancies. DESIGN: Randomized Controlled Trial PATIENTS AND METHODS: This study was done at obstetrics and Gynaecology Department unit 3 Lady willingdon Hospital / king Edward medical university Lahore for a period of six months from 1.7.2014 to 31.12.2014. 100 pregnant postdate women were divided equally in two groups randomly. Group A was induced with IMN (40mg) applied in posterior fornix of vagina followed by Misoprostol (50ug) and Group B, was induced by Misoprostol (50ug) alone. Efﬁcacy of both methods of induction was compared. RESULTS: In this study mean age in group-A and group-B was 24.53 ± 4.65 years and 24.98 ± 4.87 years respectively. A total of 42(84%) in group-A and 38(78%) in group – B had had gestational age 4041 weeks while 42 gestational age was calculated in 8(16%) of group-A and 11(22%) of group-B. Efﬁcacy of both treatments were compared using Chi-square test, so in group-A efﬁcacy was higher (68%) as compared to group-B (34%), p-value = 0.001. CONCLUSION: The results of the study revealed that intravaginal administration of IMN plus Misoprostol is more effective than Misoprostol alone for labour induction in post term pregnancies.